Exploring native and non-native teachers’ beliefs on the use of the mother tongue in the English language learning classroom: A qualitative investigation - Cortan, Daniel (2016)
Abstract The ideology that teaching English as a second or foreign language should not allow the use of students’ mother tongue, whether by teachers or students, has predominantly dominated language teaching methodologies for more than a hundred years. Despite this, recent paradigm shifts in beliefs, literature and empirical investigations argue for a change in practice, and thus, the perception that the mother tongue should or should not enter the domains of language learning classes draws heated debate. This qualitative investigation enters the debate by interviewing native English and non-native English speaking teachers to explore their perceptions of the above issue. Results show that whilst both groups appear to value the use or allowance of mother tongue in classrooms, it is primarily for non-pedagogical reasons. Acknowledging this, differences in opinions and contradictions in beliefs are equally evident, which may ultimately be responsible for workplace misunderstandings or methodological disagreements. Such contradictions may explain why the presence of mother tongue appears to be an inevitable phenomenon but, generally speaking, findings imply that native English speaking teachers are less likely to encounter the mother tongue in the classroom than their non-native counterparts, and as a result, are more sympathetic when it manifests itself. Although this paper enters the debate from a neutral perspective, it cannot ignore the potential of the mother tongue in aiding the learning of a second language whilst simultaneously acknowledging the dangers of its overuse. Resultantly, suggestions derived from both sides of the debate are offered. Nethertheless and to conclude, it is suggested that to keep in line with the turning tide of beliefs, teachers and institutions iv should consider integrating the mother tongue into second or foreign language teaching as a pedagogical tool in a balanced and strategic manner.